Delivering perinatal psychiatric services in the neonatal intensive care unit. (10th July 2013) - Hatters Friedman, Susan; Kessler, Ann; Nagle Yang, Sarah; Parsons, Sarah; Friedman, Harriet; Martin, Richard J.
Abstract: Aim: To describe characteristics of mothers who would likely benefit from on‐site short‐term psychiatric services while their infant is in the neonatal intensive care unit (NICU). Methods: For 150 consecutive mothers who were referred for psychiatric evaluation and psychotherapeutic intervention in an innovative NICU mental health programme, baseline information was collected. Data regarding their referrals, diagnosis, treatments and infants were analysed. Results: Most mothers were referred because of depression (43%), anxiety (44%) and/or difficulty coping with their infant's medical problems and hospitalization (60%). Mothers of VLBW infants were disproportionately more likely to be referred. A majority of mothers accepted the referral and were treated; most only required short‐term psychotherapy. A minority resisted or refused psychiatric assessment; a quarter of these had more difficult interactions with staff or inappropriate behaviours. In these cases, the role of the psychiatrist was to work with staff to promote healthy interactions and to foster maternal‐infant bonding. Conclusion: Overall, on‐site psychiatric services have been accepted by a majority of referred NICU mothers, and most did not require long‐term treatment. A considerable need exists for psychiatric services in the NICU to promote optimal parenting and interactions. Abstract :